Identifying the Requirements and Functions of Ambidextrous Management of Sports Volunteers - Zahra Karimi; Reza Andam; Hasan Bahroloolom; Abaas Rezaei (Shahid Bahonar University of Kerman, 2023)
Volunteers are valuable resources for sports organizations. Most of the sports organizations need to identify and employ the volunteers simultaneously in order to continue their activities. The present study made an effort to identify the requirements and functions of ambidextrous management of sports volunteers. Considering this aim, the meta-synthesis research method was used to carry out the study. More specifically, based on the process of the meta-synthesis research method, at the first stage, 312 papers were identified by searching the relevant databases. At the second phase, 55 papers were selected by screening the identified papers. Finally, the model of the study was developed by analyzing the selected papers. The model involved five ambidextrous requirement categories including the managerial, organizational, physical, strategic values, and motivational categories. Moreover, it comprised three ambidextrous function categories including empowering measures, opportunity-creating measures, and motivating measures categories. The sports managers can focus on the ambidextrous management requirements and the ambidextrous management functions including the empowering measures, opportunity-creating measures, and motivating measures in order to use the ambidextrous sports voltmeter management system and to exploit these human resources to achieve the goals of their organizations.